'I think this medicine actually killed my wife': patient and family perspectives on shared decision-making to optimize medications and safety. (April 2019) - Mangin, Dee; Risdon, Cathy; Lamarche, Larkin; Langevin, Jessica; Ali, Abbas; Parascandalo, Jenna; Stephen, Gaibrie; Trimble, Johanna
Background: This study explored the perspectives and experiences from patients and families around how patient/family preferences and priorities are considered in medication-related discussions and decisions within the healthcare system. Methods: We conducted a qualitative study using focus groups with residents of Southern Ontario and British Columbia ( N = 16). Three focus groups were conducted using a semi-structured focus group guide. The audiotaped focus group discussions were transcribed verbatim. A thematic analysis, using inductive coding, was completed. Results: A total of three main themes [and several sub-themes (and sub-sub-themes)] emerged from the data: patient and family expertise [ lived experience, information expert, and perceived expert roles (patient/family, healthcare provider)], perceived patient-centredness ( relationship qualities of healthcare provider and assumptions about patients ), and system ( time, coordination and communication, and culture ). Stories told by participants helped to clarify the relationships between the themes and sub-themes, leading to, what we understand as shared decision-making around medications and subsequent health outcomes. Conclusions: Our findings showed that shared decision-making resulted from both recognition and integration of the personal expertise of the patient and family in medications, and perceived patient-centredness. This is broadly consistent with the current conceptualization of evidence-based medicine. The stories told highlight the complex, dynamic, and nonlinear nature of shared decision-making for medications, and that patient priorities are not as integrated into shared decision-making about medications as we would hope. This suggests the need for developing a systematic process to elicit, record, and integrate patient preferences and priorities about medications to create space for a more patient-centred conversation.